Hopeful tourism to grapple and engage with emotions in the Anthropocene. (26th July 2022) - Westoby, Ross; Clissold, Rachel; McNamara, Karen E.
Abstract: The Anthropocene is characterised by people's significant influences on global systems, which generate both high levels of uncertainty and profound change in our lifetime. We must start to better engage with what it might mean to inhabit and know the world differently, especially as we experience extensive loss and change, and because grief is increasingly with us. At the same time, we must better engage with our emotions productively and find hope through active, conscious processing and mourning. In this commentary, we explore the potential of engaging in nature‐based tourism to help us grapple with, process,  and positively engage with the emotions of the Anthropocene. We gained insights about such potential for healing by collaborating with two eco‐tourism enterprises in Australia: Mount Barney Lodge in Southeast Queensland and Salt and Bush Eco Tours in the Peel River Region on the west coast of Australia. We found that nature immersion can heal and renew. Moreover, guides who know about and are connected to or living closely with nature play critical roles as interpreters or intermediaries with nature. They can also inspire gratitude and positive emotions by encouraging us to (re)connect with nature and provide new and transformative perspectives that bring comfort and motivate action. Abstract : We engage with ideas about what it might mean to be of the Anthropocene by exploring ways to grapple and productively engage with our grief and anxiety. Drawing from our exploration of our own and others' experiences of nature‐based tourism, we point to important functions for these enterprises and their guides for such outcomes.